Multiculturalism in Elementary Education: An Implementation of Inclusive Strategies to Foster Tolerance - Sandi Pradana; Ema Puspitasari; Ulyati Retno Sari (Madiha Press, 2024)
Multiculturalism in elementary education is essential for fostering inclusivity and tolerance in increasingly diverse societies. This study examines inclusive strategies for implementing multicultural education to cultivate understanding, empathy, and social harmony among students. Utilizing a qualitative approach with a literature review methodology, data was collected from scholarly sources, including academic journals and policy reports. The findings highlight the effectiveness of culturally responsive curricula, teacher training in multicultural competence, and the use of interactive media in enhancing students’ engagement and respect for diversity. However, challenges such as limited resources, inadequate teacher training, and attitudinal barriers persist. This study underscores the need for collaborative efforts to overcome these challenges and ensure the successful integration of multicultural principles in elementary education.